ZIF-8-coated 3D-printed PCL/ion-doped BCP scaffolds for enhanced bone regeneration - Vahid Khademi Ardakani; Niloufar Boroumand; Ghasem Dini; Mohsen Golabi; Maryam Abdollahi Asl (PLoS ONE, 2026)
Large bone defects require bioactive, mechanically robust scaffolds for regeneration. This study developed 3D-printed polycaprolactone/biphasic calcium phosphate (PCL/BCP) composite scaffolds (35−45 wt% ion-doped BCP with Sr 2+ , Mg 2+ , and Si 4+ ) via fused deposition modeling (FDM), followed by in situ ZIF-8 coating. The optimal PCL + 40 wt.% ion-doped BCP formulation exhibited superior compressive strength (~30 MPa) and modulus (~ 0.4 GPa). Degradation in Phosphate-buffered saline (PBS) showed ~8% mass loss over 28 days with stable pH. Immersion in simulated body fluid (SBF) revealed rapid apatite formation and sustained release of Ca 2+ , P, Mg 2+ , Si 4+ , and Sr 2+ ions. SEM confirmed uniform nanoscale ZIF-8 deposition, enriching surfaces with Zn 2+ . In vitro assays with MG-63 cells and hBMSCs demonstrated that ZIF-8-coated scaffolds significantly enhanced cell adhesion, proliferation (MTT), cytoskeletal organization (DAPI/phalloidin), and mineralization (Alizarin Red S) compared to uncoated controls (p < 0.05). The synergistic integration of ion-doped BCP, 3D printing, and ZIF-8 coating yields a bioactive, biodegradable platform with excellent osteogenic potential for advanced bone tissue engineering.